Incident arrhythmias, heart failure and cardiovascular outcomes with SGLT-2 inhibitor use in diabetic patients: Insights from a global federated electronic medical record database. (19th May 2022) - Fawzy, AM; Rivera-Caravaca, JM; Fauchier, L; Lip, GYH
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Sodium-glucose co-transporter 2 inhibitor (SGLT-2i) use has been associated with improved outcomes in patients with prevalent heart failure (HF), regardless of whether or not they have diabetes. Purpose: We aimed to investigate the impact of SGLT-2i use on the risk of incident HF and adverse cardiovascular outcomes in patients with diabetes. Methods: All diabetic patients between January 2018 and December 2019 were identified from a federated electronic medical record database (TriNetX), and followed up for 2 years. A 1:1 propensity score matched (PSM) analysis was performed to balance SGLT-2i and non-SGLT-2i cohorts. The primary outcome was incident HF and secondary outcomes included all-cause mortality, cardiac arrest, ventricular tachycardia/fibrillation (VT/VF), incident atrial fibrillation (AF), ischaemic stroke, a composite of arterial and venous thrombotic events, and a composite of incident VT/VF and cardiac arrest. Results: A total of 115, 749 diabetic patients who were on SGLT-2i and 2, 316, 638 who were not on SGLT-2i were identified. After PSM, 115, 749 patients remained in each group. In the PSM analysis, the risk of incident HF was significantly lower in patients who were on SGLT-2i, compared to patients who were not on SGLT-2i (hazard ratio [HR] 0.67, 95% confidence interval [CI] 0.65-0.70). SGLT-2i use was also associated with a significantly lower risk of all-cause mortality (HR 0.62, 95% CI 0.59-0.65), cardiac arrest (HR 0.62, 95% CI 0.55-0.69), incident AF (HR 0.78, 95% CI 0.75-0.81), ischaemic stroke (HR 0.93, 95% CI 0.88-0.96), composite arterial and venous thrombotic events (HR 0.93, 95% CI 0.90-0.95), and composite of incident VT/VF and cardiac arrest (HR 0.74, 95% CI 0.68-0.79), compared to SGLT-2i non-use. There were no significant differences between the two groups for VT/VF (HR 0.94, 95% CI 0.88-1.01). Conclusion: SGLT-2i use was associated with a significant decrease in the risk of incident HF, all-cause mortality, cardiac arrest, incident AF, ischaemic stroke, thromboembolic events and VT/VF/cardiac arrest, when compared to the non-use of SGLT-2i.